PENDUGAAN STOK IKAN PARI MONDOL (HIMANTURA GERRARDI) YANG DIDARATKAN DI PPI SUKADANA KECAMATAN SUKADANA KABUPATEN KAYONG UTARA KALIMANTAN BARAT - Aprilianto, Dwi; Inpurwanto, Inpurwanto; Soetignya, Widadi Padmarsari (Jurnal Sains Mahasiswa Pertanian, 2020)
By stock assessment, data on the current status of fish resource utilization in nature are obtained, which are used for optimum utilization of fish resources and prevent overuse of fish resources, so that fish resources can be used sustainably. This research was conducted to assess the stocks of mondol stingray stock which included the frequency distribution width, the relationship between width and weight, growth and mortality and the rate of exploitation. This study uses a census method by observing the stingray caught by fishermen. Stingray samples were taken weekly for four months, at the fish landing sites. The data obtained were analyzed using Microsoft Excel and FISAT II software by FAO-ICLARM. The number of mondol rays obtained during the study was 238, consisting of 118 males and 120 females. The wide range of mondol rays obtained was 170-640 mm (male) and 180-810 mm (female), and the weight range was 170-8,405 g (male) and 195-16,877 g (female). The relationship between the width-weight of male and female mondol showed a negative allometric growth pattern. Analysis of the growth of mondol stingrays shows the growth coefficient of male stingrays is 0.38 per year and females 0.40 per year. The mortality of mondol rays was caused more by fishing mortality than natural mortality. The calculation of the exploitation rate of mondol stingray shows the occurrence of overfishing. Keywords: Mondol Stingray, Stock Assessment, Sukadana District